2020
DOI: 10.1108/intr-09-2018-0417
|View full text |Cite
|
Sign up to set email alerts
|

Data quality comparison between computers and smartphones in different web survey modes and question formats

Abstract: PurposeLow response rates in web surveys and the use of different devices in entering web survey responses are the two main challenges to response quality of web surveys. The purpose of this study is to compare the effects of using interviewers to recruit participants in computer-assisted self-administered interviews (CASI) vs computer-assisted personal interviews (CAPI) and smartphones vs computers on participation rate and web survey response quality.Design/methodology/approachTwo field experiments using two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…Additionally, we found that the length of answers to open-ended questions was shorter on smartphones compared to computers. This finding is in line with the results of previous studies (Ha et al, 2020; Struminskaya et al, 2015). We also analyzed the level of differentiation in specific questions.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Additionally, we found that the length of answers to open-ended questions was shorter on smartphones compared to computers. This finding is in line with the results of previous studies (Ha et al, 2020; Struminskaya et al, 2015). We also analyzed the level of differentiation in specific questions.…”
Section: Discussionsupporting
confidence: 94%
“…Regarding the length of responses to open-ended questions, most studies indicated shorter responses on tablets and especially on smartphones compared to computers (Ha et al, 2020;Mavletova, 2013;Struminskaya et al, 2015) or found no differences (Antoun, Katz, et al, 2017;Schlosser & Mays, 2018). Concerning distractions or multitasking behavior that can affect data quality, research found that respondents using a smartphone or a tablet seemed to show less multitasking behavior when passively measured via paradata (data on the data collection process automatically collected by the online survey software; De´cieux, 2022;Ho¨hne et al, 2020).…”
Section: Research On Device Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Another concern is that while kiosk surveys are used to evaluate business practices and customer satisfaction, they have been used in health education and public knowledge assessment projects in a limited capacity 43‐45 . It is reasonable to suggest that kiosk interaction is similar to online surveying which has in general been considered to be very useful, 46‐48 suggesting that the results here can be useful with reservations.…”
Section: Resultsmentioning
confidence: 99%